Enhancing performance of Tall-Skinny QR factorization using FPGAs - Rafique, Abid (2015)
Communication-avoiding linear algebra algorithms with low communication latency and high memory bandwidth requirements like Tall-Skinny QR factorization (TSQR) are highly appropriate for acceleration using FPGAs. TSQR parallelizes QR factorization of tall-skinny matrices in a divide-and-conquer fashion by decomposing them into sub-matrices, performing local QR factorizations and then merging the intermediate results. As TSQR is a dense linear algebra problem, one would therefore imagine GPU to show better performance. However, the performance of GPU is limited by the memory bandwidth in local QR factorizations and global communication latency in the merge stage. We exploit the shape of the matrix and propose an FPGA-based custom architecture which avoids these bottlenecks by using high-bandwidth on-chip memories for local QR factorizations and by performing the merge stage entirely on-chip to reduce communication latency. We achieve a peak double-precision floating-point performance of 129 GFLOPs on Virtex-6 SX475T. A quantitative comparison of our proposed design with recent QR factorization on FPGAs and GPU shows up to 7.7× and 12.7× speed up respectively. Additionally, we show even higher performance over optimized linear algebra libraries like Intel MKL for multi-cores, CULA for GPUs and MAGMA for hybrid systems.